Joint mobilization improves spatiotemporal postural control and range of motion in those with chronic ankle instability - Hoch, Matthew C.; McKeon, Patrick O. (Journal of orthopaedic research, 2011)
The purpose of this study was to examine the effects of a single joint mobilization treatment on dorsiflexion range of motion (DF ROM), posterior talar glide, and dynamic and static postural control in individuals with self‐reported chronic ankle instability (CAI). In this randomized cross‐over study, subjects received a Maitland Grade III anterior‐to‐posterior joint mobilization treatment and a control treatment of rest for 5 min. Weight‐bearing DF ROM, instrumented posterior talar displacement and posterior stiffness, the anterior, posteromedial, and posterolateral reach directions of the Star Excursion Balance Test (SEBT), and time‐to‐boundary (TTB) single‐limb stance static postural control were assessed on both treatment days in 9 males and 11 females with CAI. The results indicated that the joint mobilization treatment was associated with significantly greater DF ROM (p = 0.01) and TTB in the anterior–posterior direction with eyes‐open (p < 0.05). Although not significant, trends were identified in posterior talar displacement (p = 0.08) and the mean of TTB in the medial‐lateral (ML) direction (p = 0.07). No significant differences were observed in the standard deviation of TTB in the ML direction, the SEBT, or posterior stiffness (p > 0.05). This indicates that a single joint mobilization treatment has mechanical and functional benefits for addressing impairments in sensorimotor function and arthrokinematic restrictions commonly experienced by individuals with CAI. © 2010 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 29:326–332, 2011